2015
DOI: 10.1038/srep16429
|View full text |Cite
|
Sign up to set email alerts
|

Transdifferentiation of periodontal ligament-derived stem cells into retinal ganglion-like cells and its microRNA signature

Abstract: Retinal diseases are the leading causes of irreversible visual impairment and blindness in the developed countries. Human retina has limited regenerative power to replace cell loss. Stem cell replacement therapy has been proposed as a viable option. Previously, we have induced human adult periodontal ligament stem cells (PDLSCs) to the retinal lineage. In this study, we modified our induction protocol to direct human adult PDLSCs into retinal ganglion-like cells and determined the microRNA (miRNA) signature of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
45
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 51 publications
(47 citation statements)
references
References 43 publications
(69 reference statements)
1
45
0
Order By: Relevance
“…On the contrary, stem cells from human PDL, are easily accessible, and become an autologous cell source for neural therapy . Human PDLSCs are multipotent in nature and can be induced to differentiate into different lineages, including neuronal lineage . In this study, we demonstrated the PDLSC‐mediated RGC protection in a rat model of ONC.…”
Section: Discussionmentioning
confidence: 62%
See 2 more Smart Citations
“…On the contrary, stem cells from human PDL, are easily accessible, and become an autologous cell source for neural therapy . Human PDLSCs are multipotent in nature and can be induced to differentiate into different lineages, including neuronal lineage . In this study, we demonstrated the PDLSC‐mediated RGC protection in a rat model of ONC.…”
Section: Discussionmentioning
confidence: 62%
“…Human PDLSC lines were previously established and characterized . They were maintained in 1:1 Dulbecco's modified Eagle's medium/F‐12 medium (DMEM/F12; Gibco BRL, Rockville, MD) supplemented with 10% heat‐inactivated fetal bovine serum (Gibco BRL) and 1× penicillin‐streptomycin (P/S; Gibco BRL).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…ARPE-19 cell integrity was examined by the immunofluorescence analysis of tight junction protein (ZO-1) using our previously established protocol44. Briefly, 1 × 10 4 cells per well were seeded on a glass coverslip in a 12-well plate (Corning Life Sciences).…”
Section: Methodsmentioning
confidence: 99%
“…Human ocular cell lines, including retinal pigment epithelial (RPE) cells ARPE-19 (catalogue number: CRL-2302, American Type Culture Collection (ATCC), Manassas, VA) [11,12], lens epithelial cells B3 (catalogue number: CRL-11421, ATCC) [13], primary trabecular meshwork (TM) cells [14], and retinoblastoma cells Y79 (catalogue number: HTB-18, ATCC) [15], have been previously established. We also collected human mesenchymal stem cells (MSCs) from different sources, including bone marrow-derived MSCs (BM-MSCs; catalogue number: 7500; ScienceCell Research Laboratories, Carlsbad, CA) [16], adipose-derived stem cells (ASCs) [17], and periodontal ligament-derived stem cells (PDLSCs) [18,19]. Other human tissue cell lines, such as human umbilical vein endothelial cells (HUVEC; catalogue number: CRL-1730, ATCC), lung epithelial carcinoma cells A549 (catalogue number: CCL-185, ATCC), liver hepatocellular carcinoma cells HepG2 (catalogue number: HB-8065, ATCC) and epidermal keratinocytes HaCaT (catalogue number: T0020001, AddexBio, San Diego, CA), were also investigated in this study.…”
Section: Human Cell Lines and Mouse Tissuesmentioning
confidence: 99%